Intracranial Germinoma Misdiagnosed as Hyperthyroidism: A Case Report and Review of the Literature - Tian, Juan; Wu, Jialu; Yan, Zhe; Huang, Hui (Frontiers in Endocrinology, 2022)
Intracranial germ cell tumors（GCTs） are relatively rare, which account for 0.5 % of all primary intracranial neoplasms. Intracranial germinomas most commonly occur in the pineal and suprasellar region, making up the majority of all intracranial GCTs. For its diversified clinical manifestations, the diagnosis is easily confused with other diseases. Here, we present a case of a 19-year-old boy with intracranial germinoma who was preliminarily misdiagnosed as hyperthyroidism for the symptoms of weight loss and thyroid dysfunction.